Case Report: A 72-Year-Old Woman With Progressive Motor Weakness, Dry Eyes and High Levels of Serum Neurofilament Light Chain - Wendebourg, Maria Janina; Kuhle, Jens; Hardmeier, Martin (Frontiers in Neurology, 2022)
Background Diagnosis of Amyotrophic Lateral Sclerosis (ALS) is challenging as initial presentations are various and diagnostic biomarkers are lacking. The diagnosis relies on the presence of both upper and lower motor neuron signs and thorough exclusion of differential diagnoses, particularly as receiving an ALS diagnosis has major implications for the patient. Sjögren's syndrome may mimic peripheral ALS phenotypes and should be considered in the work-up. Case A 72-year-old female presented with a mono-neuropathy of the right leg and a complaint of dry eyes and mouth. Initial diagnostic work-up confirmed a regional sensorimotor neuropathy and a Sjögren's syndrome; a causal relationship was assumed. However, motor symptoms spread progressively despite immunosuppressive treatment, eventually including both legs, both arms and the diaphragm. Clinically, unequivocal central signs were lacking, but further along in the disease course, the atrophy pattern followed a split phenotype and deep tendon reflexes were preserved. Nerve biopsy did not show vasculitic infiltration; however, serum neurofilament light chain (sNfL) concentrations were and remained persistently highly elevated despite immunosuppressive treatment. Electrodiagnostic re-evaluation confirmed denervation in 3 regions. A diagnosis of familial ALS was finally confirmed by a C9orf 72 repeat expansion. Stationary sensory symptoms were best explained by a neuropathy associated with concomitant Sjögren's syndrome Discussion Our instructive case shows the difficulties of diagnosing ALS in the setting of a peripheral symptom onset and a concurrent but unrelated condition also causing neuropathy. Such cases require high clinical vigilance and readiness to reappraise diagnostic findings if the disease course deviates from expectation. Recently proposed simplified diagnostic criteria, genetic testing and body fluid biomarkers such as sNfL may facilitate the diagnostic process and lead to an earlier diagnosis of ALS.